2021
DOI: 10.1108/jfra-08-2021-0245
|View full text |Cite
|
Sign up to set email alerts
|

Does earnings management mediate the relationship between audit quality and company performance? Evidence from Jordan

Abstract: Purpose The purpose of this study is to look at the direct relationship between audit quality, earnings management (EM) practices and company performance, as well as the indirect influence (mediation) of EM practices in the relationship between audit quality and company performance. It offers empirical evidence from the Jordanian market, which is considered an emerging market. Design/methodology/approach The population of this study is represented in Jordanian service companies listed on the Amman Stock Exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 92 publications
3
21
0
Order By: Relevance
“…However, other empirical studies (Afifa et al, 2021b) noted that company accomplishment is negatively affected by EMP, where managers use earnings management by accruals to reduce the company performance to avoid paying taxes and fees, therefore, negatively affects CV. Martowidjojo et al (2019) concluded that high earnings quality reduces rather than raises the market value of shares but that companies that pay dividends are priced considerably higher.…”
Section: Earnings Management Acts As Mediating Rolementioning
confidence: 98%
See 4 more Smart Citations
“…However, other empirical studies (Afifa et al, 2021b) noted that company accomplishment is negatively affected by EMP, where managers use earnings management by accruals to reduce the company performance to avoid paying taxes and fees, therefore, negatively affects CV. Martowidjojo et al (2019) concluded that high earnings quality reduces rather than raises the market value of shares but that companies that pay dividends are priced considerably higher.…”
Section: Earnings Management Acts As Mediating Rolementioning
confidence: 98%
“…Consequently, many business-relevant decision-makers have become involved in the issues of governance, auditing, monitoring and ensuring the business efficiency to minimize the level of EMP (Inaam and Khamoussi, 2016). Inaam and Khamoussi (2016) and Afifa et al (2021b) have shown that both audit and control efficiency negatively affect EMP in businesses. The high auditing and monitoring quality helps to improve the credibility of the fiscal information disclosed, which guides to improving the levels of confidence that shareholders, funders and other involved parties give to these businesses (Krishnan, 2003;Wijaya, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations